Climate Change and the Challenges Faced by the Amazonia - de Menezes Franco, Marco Aurélio (Cadernos de Astronomia, 2025)
The Amazon, one of the most biodiverse biomes on the planet, plays a crucial role in global climate regulation and the hydrological cycle of South America. However, climate change and the intensification of human activities, such as deforestation and wildfires, have significantly impacted the region’s ecological stability. This article analyzes the effects of land-use changes on the Amazonian climate, emphasizing the relationship between forest degradation, greenhouse gas emissions, and alterations in precipitation patterns. It also discusses the impacts of atmospheric pollution, including locally and transcontinentally sourced aerosols, which affect the radiative balance and rainfall formation. Given this scenario, the need for strict environmental policies and international cooperation is reinforced to mitigate the effects of climate change and preserve the biome’s resilience. The upcoming COP 2025 in Belém do Pará is highlighted as a strategic opportunity to strengthen global commitments to forest conservation and environmental impact mitigation.
Keywords: Amazon; climate change; land use